LEGAL REMEDIES AGAINST BANKRUPTCY DECISION FOLLOWING CONSTITUTIONAL COURT DECISION NO. 23/PUU-XIX/2021 - Pratama, Gede Aditya; Zainab, Nina; Siswanto, Heru (Faculty of Law Universitas Padjadjaran, 2023)
Bankruptcy is a legal institution created as a way out of debt problems that befall debtors. The bankruptcy mechanism consists of the Postponement of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang/PKPU) and bankruptcy itself. These two mechanisms have different legal consequences, especially regarding the available legal remedies, which differ between bankruptcy rulings originating from PKPU applications and those originating from bankruptcy applications. The available legal remedies also differ between bankruptcy rulings originating from applications submitted by debtors and those submitted by creditors. Constitutional Court Decision No. 23/PUU-XIX/2021 has changed the legal remedies provisions in Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Prior to the Constitutional Court's decision, there was no opportunity for debtors to file legal remedies against a bankruptcy ruling caused by the rejection of a peace agreement due to the failure to reach an agreement in the PKPU process. However, after the issuance of Constitutional Court Decision No. 23/PUU-XIX/2021, this has changed with the opening of the opportunity for legal remedies in the form of cassation against a bankruptcy ruling due to the rejection of a peace agreement because an agreement was not reached in the PKPU process. It is important to avoid the PKPU process being used as a means to bankrupt debtors who are still solvent but are bankrupted because there are interests of business competition involved.